Comparative study of different milk feeding systems in orphan kids - RAMGOVIND, RAMGOVIND; JOSHI, H C; PATEL, B H M; VERMA, M R; FAHIM, A H; DUTT, T (The Indian Journal of Animal Sciences, 2012)
The present study was conducted to test a group milk feeding device developed by Farm machinery and Power Workshop, IVRI for feeding orphan kids. Ten suckling kids were placed in natural suckling group (T1). The kids born which were not accepted by dam were considered as orphan. Among orphan kids, 10 kids each were kept in individual bottle feeding (T2) and group milk feeder (GMF) T3 group. The experiment was conducted for 90 days. Body weight gain, time and labour required under different feeding systems were recorded. The average body weights at the end of the experiment for the corresponding treatment groups were 11.230, 6.69±0.53 and 10.77±0.58 kg respectively. The body weight gain in T2 and T3 did not differ significantly in first month but differed significantly (P<0.05) in second month. However, in third month body weight gain did not differ significantly between T1 and T3. The ADG in groups T1 was higher followed by T3 and T2. Between artificial feeding systems, T3 group required less time than T2 group. Time require for milk feeding at the end of experiment in evening session were 1.41±0.13, 1.06±0.04 and 0.32±0.02 min. respectively which differed significantly (P< 0.05) between the groups. The labour (man-min) required during first 15 days irrespective of morning/evening sessions ranged from 23–24 min. in group T2. However, 15 days onwards man- min requirement reduced greatly. Similar trend has been observed in GMF. The average man –min in GMF ranged from 8–9 min. earlier to 15 days and subsequently reduced to 4 min. in rest part of experimental period. Incidence of diarrhea was very less in GMF (20%) compared to bottle feeding (40%). It can be concluded that Group Milk Feeding device helped in saving the time and labour without affecting the body weight gain of orphan kids in comparison to bottle feeding.